A.The การวิเคราะห์การบริหารรัฐของราชวงศ์ศรีวังสาด้านการเผยแผ่ศาสนาอิสลามรัฐปาตานี - สิเดะ, แวยูโซะ (Al-HIKMAH Journal, 2021)
Abstract This research article The objective of this study was to study the method of religious change of Pattani society in the past. To analyze the state administration of the Siwangsa dynasty on the missionary mission of the Patani state of the past. By studying and researching information from documents History book of peoples and ethnicities living on the Malay Peninsula. History of the Sri Wang Sa dynasty History of the Islamic Government of Patani And various academic texts related The analysis of the data was conducted inductive, that is, to draw conclusions from what appeared while collecting data according to the general research process and presenting the analysis results after the sub-points were obtained. And to formulate a descriptive report The study found that: 1) the administration of the Islamic State Since Islam is the religion that regulates all human rules. And for humans to perform their mission only as representatives of Allah. 2) The approach to advocating for religious calls is the introduction of strategies. And a call to invite to religion The support is as follows: a. The approach to support in the Qur'an context is to promote the establishment of a formal organization that allows people in the body to gain complete knowledge. And recruiting people to spread knowledge to the general community As well as safeguarding in a reasonable way for religion to remain with the society, market, time. B. Guidelines for advocacy and administration of religion. In the historical context of Islam, the Havari people who were the supporters of Islam in the time of the Prophet nabi isa time were sacrificed in both physical and spiritual propagation. 3) Determination of the area of the Malay Peninsula There are views of defining that area as follows: a) Perspectives of the Malays is the peninsula inhabited by the Malays. B) the Malays and the Sriwangsa dynasty. 4) Guidelines for the administration of the Islamic propagation of the Siwangsa dynasty are as follows: a) Supporting the royal residence b) Relocation of religious institutions from the palace to the village for safety c) the establishment of a pondok institute. Keywords: State administration, Siwangsa dynasty, Islamic Propagation, Patani state